The Effect Of Democratic Leadership And Work Discipline On Employee Performance - Theresia Adisanti H. Klau; Ni Putu Nursiani; Yonas Ferdinand Riwu (Jurnal Mirai Management, 2025)
This study aims to describe Democratic Leadership Style, work discipline and employee performance and analyze Democratic Leadership Style and work discipline partially and simultaneously on employee performance. The research method used in this study is descriptive method. The type of research used is quantitative. The sample used in this study were employees of KOPDIT Serviam Oebufu Branch with a sample size of 35 sample respondents in this study. The primary data collection technique used a questionnaire technique. The results of the study showed that Democratic Leadership Style did not have a significant positive effect on Employee Performance, Work Discipline had an effect on employee performance, thus the higher the level of employee discipline in working, the higher their performance, Democratic Leadership Style and Work Discipline together had an effect on employee performance at KOPDIT Serviam Oebufu Branch.